Reducing opioid related deaths for individuals who are at high risk of death from overdose: a co-production study with people housed within prison and hostel accommodation during Covid-19 - Campbell, Anne; Millen, Sharon; Guo, Li; Jordan, Uisce; Taylor-Beswick, Amanda; Rintoul, Chris; Diamond, Aisling (Frontiers in Public Health, 2023)
Background A record number of Opioid-related deaths occurred in Northern Ireland in 2021 and it is acknowledged that the Covid-19 pandemic compounded drugs related deaths crisis. This co-production study set out to refine the design of a wearable device for Opioid users to detect and subsequently prevent a potential overdose situation. Method Purposive sampling was used to recruit people who had substance use disorders and were living in a hostel and prison during the Covid-19 pandemic. Principles of co-production influenced the study, which encompassed a focus group phase and a wearable phase. The initial phase included three focus groups with participants who inject Opioids and one focus group with workers from a street injector support service. During the wearable phase, the participant group tested the feasibility of the wearable technology in a controlled environment. This included testing the transferability of data from the device to a backend server on the cloud. Results All focus group participants expressed an interest in the wearable technology when it was presented to them and agreed, that in principle, such a device would be extremely beneficial to help reduce the risk of overdose within the active drug using community. Participants outlined factors which would help or hinder the design of this proposed device and their decision to wear it, if it were readily available to them. Findings from wearable phase indicated that it was feasible to use a wearable device for monitoring Opioid users’ biomarkers remotely. The provision of information regarding the specific functionality of the device was considered key and could be disseminated via front line services. The data acquisition and transfer process would not be a barrier for future research. Conclusion Understanding the benefit and disadvantages of technologies such as a wearable device to prevent Opioid-related deaths will be critical for mitigating the risk of overdose for people who use Heroin. It was also clear that this would be particularly relevant during Covid-19 lock-down periods, when the effects of the pandemic further exacerbated the isolation and solitude experienced by people who use Heroin.